Implementation of the Role of Watchdog by the Daily Newspaper in the Organization of the Hajj Worship In 2012 - Syaipul Hadi (Budapest International Research and Critics University, 2022)
The data generated in this study were taken from the object of research, namely the news in SKH Banjarmasin Pos and Republika about the implementation of the pilgrimage in January - December 2012. This research uses the content analysis method as a method to observe and describe the content of communication messages in mass media. The content analysis method is defined by Barelson as a research technique for an objective, systematic and quantitative description of the embodiment of communication content. The results of this research are the content of the news about the implementation of the pilgrimage in Republika daily is dominated by news on the activities of the pilgrimage with a percentage of 69.7%. News that is in favor of the interests of the wider community with a percentage of 83.2%. There is only 45.3% of the news in large and continuous quantities, most of which lack data, which means that the evidence presented is relatively low at 76%. The news only describes the activities of the pilgrimage there is 63.9%. Most of them have Significant, Timelines, Magnitude, Proximity, and Factual values, namely 36.1%. Resource persons from figures who criticize the implementation of Hajj are only used in 25.2%. News as much as 46.2% use news features. News with the theme of the Hajj ritual is 42.0%. As many as 46.2% of the news content tends to support the assessment that the implementation of the Hajj has been good. A total of 64.7% of the news was presented descriptively. The news content in the Banjarmasin Post is dominated by news on hajj activities with a percentage of 73.6%. News that is in favor of the interests of the wider community with a percentage of 73.6%. Unsustainable news 73.6%. News with less strong evidence 56.6%. The news only describes 56.7% of the pilgrimage activities and as many as 22.6% use sources from the organizers of the pilgrimage. Soft news is 30.2%. News with the theme of the Hajj ritual is 37.7%. A total of 37.7% tend to support the assessment that the implementation of the pilgrimage is good, and as much as 56.6% is presented descriptively.